Opportunities and challenges of a community-based bull breeding programme: a case of the regional pastoral livelihood resilience project in Uganda - Ssekibaala, Gonzaga; Ilukor, John; Walusimbi, Sadhat (My University, 2024)
The Regional Pastoral Livelihood Resilience Project Community-Based Breeding Programme (CBBP) was designed with the objective of increasing production and productivity of local Zebu cattle by introducing Sahiwal bulls among sedentary and agro-pastoral livestock farmers. This study mapped out actors, their roles and level of influence in the CBBP as well as the opportunities and challenges encountered during its implementation using the Process Net-Map tool. The results revealed that there were differences in number and type of influential actors between sedentary and agro-pastoral livestock farmers. The bull host and subcounty veterinary officer were the most influential actors among the sedentary livestock farmers whereas it was the herdsman, bull host, and Community Animal Health Workers (CAHWs) among the agro-pastoral farmers. The CBBP was associated with benefits such as increased market value for cattle, reduced chances for cattle rustling, increased cattle productivity in terms of milk and beef production volumes and ease of access to veterinary services. In contrast, the challenges encountered were related to both governance (limited availability of veterinarians, cattle rustling, exclusion of farmers in the planning phase of the CBBP, political interference and failure of collective action) and bull management (high costs of keeping and maintaining the bulls in terms of feeding, housing, watering and veterinary care, heavy bulls injuring or breaking the small cows, sexually transmitted reproductive diseases among others). Lastly, this paper recommends adoption of a combination of well-organized and facilitated Artificial Insemination (AI) programmes alongside the improved bull service scheme as each has capacity to address the challenges of another.